Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1007/s11242-004-1489-0
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Radon Transport through Building Materials: Influence of the Water Content on Radon Exhalation Rate

Abstract: Radon transport in porous materials is strongly influenced by the presence of water. It is also necessary to be able to numerically control the effects of this parameter. The radon concentration and radon exhalation rate have been determined by simulation in various building materials containing an increasing water content. It has been proved that the presence of water does not involve the same variations in the concentration on the surface of the medium, according to its porosity. For porous media with low po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 18 publications
0
10
0
1
Order By: Relevance
“…The details of the continuous radon monitor described elsewhere [36]. The growth of radon concentration in a chamber of volume 'V' is given by [37].…”
Section: Measurement Of Radon Exhalation Rates Of Mortarmentioning
confidence: 99%
“…The details of the continuous radon monitor described elsewhere [36]. The growth of radon concentration in a chamber of volume 'V' is given by [37].…”
Section: Measurement Of Radon Exhalation Rates Of Mortarmentioning
confidence: 99%
“…It is known that the radon emanation coefficient under saturated conditions is smaller than that under dry conditions, whatever the building material (Fournier et al, 2005). This behavior stems from the fact that the recoil distance of the radon atoms in air is about 900 times higher than in water.…”
Section: Stage I (Dormant Period)mentioning
confidence: 99%
“…At the same time, the presence of water in a porous medium is known to dramatically influence radon diffusion. For example, Fournier et al (2005) found recently that radon diffusion coefficient in cement decreases from w1 Â 10 ÿ2 (dry material) to w2 Â 10 ÿ6 m h ÿ1 (saturated material).…”
Section: Stage I (Dormant Period)mentioning
confidence: 99%
“…6). L'ensemble des résultats obtenus par simulation a offert de très bonnes corrélations avec les expériences réalisées en laboratoire sur des matériaux de construction de caractéristiques similaires (Fournier et al, 2005a(Fournier et al, , 2005b.…”
Section: Les Mécanismes De Transport Et Le Rôle De L'eauunclassified